2023 State of Climate Services: Health - World Meteorological Organization (United Nations, 2023)
The interconnection between climate and health is undeniable. The climate, exacerbated by climate change, poses systematic and serious threats to human health. Climate change is documented to be impacting human health in many complex ways, including by leading to death, injury and illness from heat stress, the disruption of ecosystems and food systems, increases in food-, and water- and vector-borne diseases, and exposure to air pollution. The 2023 edition of the WMO State of Climate Services report focuses on health, which highlights the importance of climate services and information in protecting lives and livelihoods. While there are many good examples of how countries are successfully using climate information and services to detect, monitor, predict and manage climate-related health risks, there is huge potential for enhancing the impact of climate science and services for health. This report examines the current state of climate services for health, and presents a series of next steps, recommendations and case studies.